Transformasi Peran Kiai Sebagai Pendidik Di Era Revolusi Industri 4.0 - Bayu Adi Rangga; Muhamad Akip; Selamat; Sujarwo; Mukhlas (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This study examines the transformation of the role of kiai (Islamic scholars) in pesantren education in the era of the Industrial Revolution 4.0. The purpose of this research is to analyze how kiai adapt to digital technology, strengthen digital competencies, integrate Islamic values with technology, and exercise transformational leadership in guiding students. The study employs a qualitative approach with a literature review and field observation as primary methods. Data were collected from interviews with kiai, observations of pesantren digital learning practices, and analysis of digital educational content. The findings indicate that kiai play a pivotal role as agents of innovation, ethical digital literacy mentors, and leaders in integrating technology with traditional Islamic education. Digital competencies in technological, pedagogical, and ethical dimensions enable kiai to implement blended learning, develop interactive educational media, and guide students in producing valuable digital content. Furthermore, transformational leadership by kiai fosters student creativity, critical thinking, and moral development, ensuring that technology enhances rather than undermines Islamic educational values. The study concludes that the transformation of kiai roles is essential for sustaining the relevance, quality, and ethical integrity of Islamic education in the digital era.